Effect of indol-3-butric acid and chloromequate chloride on the vegetable and fruit growth of tomato plants - Ah. A. Suliman; A. G. Abramov (Овощи России, 2020)
Relevance. This study aimed to improve fruit set and plant performance to increase tomato productivity by studying the effect of plant growth regulators on tomato plants.Methods. A specific experiment has been carried out to study the effect of plant growth regulators Milagro (1% indol-3-butric acid) and Atlet active substances indol-3-butric acid and chloromequate chloride with applied doses (0.6 M/L, 1.0 M/L and 1.5 M/L) and (1.0, 1.5 and 2.0 M/L) on growth and physiological characteristics of plants (Big Beef F1). The experimental design was a Complete Randomized Blocks Design. Both Hemo bles was applied three times (spraying on plants at 30 DAP, spraying on plants at 60 DAP and spraying on plants 90 DAP).Results. The obtained results showed that, Applying Milagro (1% indol-3-butric acid) had the highest significant Plant height (80.13, 128.77 and 239 cm), number of leaves/plant (18.0, 34.67 and 44.3) and stem diameter (1.07, 1.5 and 2.03 cm), fruit weight (122.0 and 136 g), Flower Clusters number in the plant (4.64, 13.33 and 16.33) and Fruits Number (61.67, 62.0 and 67) Over the three years of study. The results were analyzed using one-way analysis of variance (ANOVA) followed by Tukey’s HSD test with α = 0.05 with the help of MINITAB (v. 19.0) program.